Immediate Outcome of Balloon Pulmonary Valvuloplasty in Children: Experience at Bangladesh Shishu Hospital & Institute - Munsi, Md Abu Sayed; Akther, Maher; Paul, Nibedita (Dhaka Shishu (Children) Hospital Journal, 2024)
Introduction: Isolated pulmonary valve stenosis is a common heart defect (6-9%). Percutaneous balloon pulmonary valvuloplasty (BPV) has become the treatment of choice for the relief of severe valvular pulmonary stenosis (PS). Objective: To assess the immediate outcome of BPV in children with congenital PS at Bangladesh Shishu Hospital & Institute, Dhaka, Bangladesh. Methods: A retrospective longitudinal cohort study was carried out in Bangladesh Shishu Hospital & Institute, Dhaka, Bangladesh from January 2021 to December 2022. Thirty three patients (23 male and 10 female) with severe PS who underwent balloon pulmonary valvuloplasty were included in the study. The gradient across pulmonary valve measured pre and immediate post valvuloplasty at catheterization and by transthoracic echo was compared. Results: A total of 33 patients underwent balloon pulmonary valvuloplasty procedure. Mean age was 2.5 ±1.2 years while male 23 and female 10 with male female ratio was 2.3:1. Mean weight of the patient was 9.112±4.50 Kg. Majority of the patients (n=22, 66.6 %) were symptomatic and dyspnea on exertion was the dominant symptom (n=18, 54.5%) and 4 (12.1%) patient presented with cyanosis. All of the patients had doming pulmonary valve (n=33, 100%). Mean size of pulmonary valve by transthoracic echo was 10.23 mm and mean size of balloon was 12.6 with balloon to pulmonary valve annulus ratio was 1.22:1. The procedure was successful in 32 (n=32, 97%) as significant reductions in the right ventricular pressure from 80.36±16.45 mm Hg (pre valvuloplasty) to 23.85±8.47 mm Hg by transthoracic echo (p=0.000) and peakto- peak systolic pressure gradient across the pulmonary valve decreased from 84.03±26.3 mm Hg (pre valvuloplasty) to 22.76±10.42 mm Hg (p<0.001) (post valvuloplasty. One patient developed cardiac arrest during valvuloplasty that patient required CPR. One patient died on 2nd day of valvuloplasty due to severe right ventricular dysfunction. On post procedure echocardiography, 14(42.4%) patient developed mild PR. Mean Fluoroscopy time was 21.66 ±18.22 minute and mean total procedure time was 40.50±20.29 minute. Conclusions: Outcome of balloon pulmonary valvuloplasty in infant and children is a very safe procedure with high success but very low complications rate. DS (Child) H J 2023; 39(1): 25-29